Postnatal Weight Gain in Preterm Infants with Severe Bronchopulmonary Dysplasia - Natarajan, Girija; Johnson, Yvette R.; Brozanski, Beverly; Farrow, Kathryn N.; Zaniletti, Isabella; Padula, Michael A.; Asselin, Jeanette M.; Durand, David J.; Short, Billie L.; Pallotto, Eugenia K.; Dykes, Francine D.; Reber, Kristina M.; Evans, Jacquelyn R.; Murthy, Karna; null (American Journal of Perinatology, 2014)
Objectives To characterize postnatal growth failure (PGF), defined as weight < 10th percentile for postmenstrual age (PMA) in preterm (≤ 27 weeks' gestation) infants with severe bronchopulmonary dysplasia (sBPD) at specified time points during hospitalization, and to compare these in subgroups of infants who died/underwent tracheostomy and others.Study Design Retrospective review of data from the multicenter Children's Hospital Neonatal Database (CHND).Results Our cohort (n = 375) had a mean ± standard deviation gestation of 25 ± 1.2 weeks and birth weight of 744 ± 196 g. At birth, 20% of infants were small for gestational age (SGA); age at referral to the CHND neonatal intensive care unit (NICU) was 46 ± 50 days. PGF rates at admission and at 36, 40, 44, and 48 weeks' PMA were 33, 53, 67, 66, and 79% of infants, respectively. Tube feedings were administered to > 70% and parenteral nutrition to a third of infants between 36 and 44 weeks' PMA. At discharge, 34% of infants required tube feedings and 50% had PGF. A significantly greater (38 versus 17%) proportion of infants who died/underwent tracheostomy (n = 69) were SGA, compared with those who did not (n = 306; p < 0.01).Conclusions Infants with sBPD commonly had progressive PGF during their NICU hospitalization. Fetal growth restriction may be a marker of adverse outcomes in this population.
Keywords: nutrition; tracheostomy; growth; bronchopulmonary dysplasia